Activation‐induced changes in platelet surface receptor expression and the contribution of the large‐platelet subpopulation to activation. Issue 2 (27th January 2020) - Moroi, Masaaki; Farndale, Richard W.; Jung, Stephanie M.
Abstract: Objective: Platelet surface receptors are also present subcellularly in organelle membranes and can be expressed on the surface upon platelet activation. However, some receptors were reported to be decreased after activation. We analyzed the mechanism of activation‐dependent expression for different receptors. Methods: Flow cytometry using platelet‐rich plasma or washed platelets was used to analyze receptor‐expression changes after platelet activation by glycoprotein (GP) VI–specific agonists, crosslinked collagen‐related peptide (CRP‐XL) and convulxin (Cvx), and thrombin. Platelets prelabeled with fluorescent antibody specific for a receptor were allowed to adhere on immobilized collagen or fibrinogen and post‐stained with antibody against the same receptor labeled with another fluorophore, allowing us to differentiate preexisting receptors from newly expressed receptors. Results: Surface expression of αIIbβ3 increased in CRP‐XL–, Cvx‐, or thrombin‐stimulated platelets, but GPIb decreased due to shedding and internalization. Both total and dimeric GPVI increased in thrombin‐induced platelets, but decreased in platelets stimulated by Cvx, as a result of internalization. The larger platelets showed a greater increase in surface receptor (α2β1, αIIbβ3, GPVI, GPIb) expression upon activation compared to the smaller ones. Pre‐ and postlabeling with antibody specific for the same receptor, but conjugated with different fluorophores, allowed us to differentiate the receptors expressed on the surface of resting platelets from receptors newly exposed to the surface upon platelet activation. Conclusions: Increased receptor expressions after activation are mainly manifested in the larger platelets. On platelets adhered on fibrinogen, the newly expressed receptors, especially GPVI, are localized in the lamellipodia of the spread platelets.